2023
DOI: 10.3390/economies11020053
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Board of Directors and Corporate Financial Performance—Empirical Evidence

Abstract: The objectives of the research are to investigate the characteristics of the Board of Directors on the financial performance of the enterprise using sample data from 52 construction and real estate enterprises listed on the Vietnam stock exchange in the period 2006–2020. Using typical regression methods such as pooled OLS, FEM, REM, and assessing the defects of the research model, the FGLS method is selected. At the same time, due to the existence of endogenous phenomena and the nature of interdependence among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Bank size is measured in terms of the Natural logarithm of firm age since incorporation [51,103,179,220,227]. Enterprise size is one of the important factors contributing to the business performance of the enterprise [151]. Firm size has a significant positive relationship with firm performance [29,30,127].…”
Section: Control Variablesmentioning
confidence: 99%
“…Bank size is measured in terms of the Natural logarithm of firm age since incorporation [51,103,179,220,227]. Enterprise size is one of the important factors contributing to the business performance of the enterprise [151]. Firm size has a significant positive relationship with firm performance [29,30,127].…”
Section: Control Variablesmentioning
confidence: 99%
“…Boards of directors, typically comprising prominent shareholders, hold a pivotal position in joint‐stock companies (Nguyen & Huynh, 2023). A skilled and CSR‐competent board attracts greater investment, subsequently enhancing financial performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The sustained scholarly attention to the subject underscores the board's pivotal role. Boards not only shoulder significant corporate accountability (Banerjee et al, 2020) but also spearhead comprehensive decision-making encompassing the gamut of the firm's operations (Nguyen & Huynh, 2023). Their purview extends from orchestrating board meetings to liaising with stakeholders (Banerjee et al, 2020), as well as selecting and supervising the organization's executives and addressing critical corporate challenges (Hillman & Dalziel, 2003).…”
mentioning
confidence: 99%
“…Research on the relationship between board size and corporate performance focuses on large firms located in developed countries and produces inconclusive results. Afrifa and Tauringana (2015), Larmou and Vafeas (2010), Khanchel (2007), Kiel and Nicholson (2003), Sunday (2008), Najjar (2012), Nguimfack and Wamba (2022) and Nguyen and Huynh (2023) found that the effect of board size is positive on company performance. However, Al Manaseer et al (2012), Basu et al (2007), Florackis (2005), Husaini (2017) and Vafeas (2000) reported that the effect of board size is negative on company performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies report that board independence has a positive influence on corporate performance (see, e.g. Gani and Jermias, 2006;Krivogorsky, 2006), whereas others report that board independence has a negative influence on corporate performance (Amran and Ahmad, 2010;Cheng, 2008;Nguimfack and Wamba, 2022;Nguyen and Huynh, 2023).…”
Section: Introductionmentioning
confidence: 99%